Azithromycin in modern pediatric practice - S.O. Kramarov; V.V. Yevtushenko (Aktualʹnaâ Infektologiâ, 2020)
Azithromycin has been used in pediatric practice for many years to treat a wide range of medical problems. This review provides data on the pharmacological and pharmacokinetic properties of azithromycin. It tells about the experience of using this drug in various diseases in children and the role of azithromycin from the position of evidence-based medicine and modern international recommendations. In particular, azithromycin is recommended as the antibiotic of choice for empirical therapy and selective therapy of acute intestinal infections in children, for etiotropic treatment of pertussis, Lyme disease and for long-term therapy for cystic fibrosis. It is recommended in the treatment of respiratory infections caused by atypical pathogens.